2023
DOI: 10.3389/fphar.2023.1264842
|View full text |Cite
|
Sign up to set email alerts
|

Novel potential pharmacological applications of dimethyl fumarate—an overview and update

Giorgia Bresciani,
Federico Manai,
Sergio Davinelli
et al.

Abstract: Dimethyl fumarate (DMF) is an FDA-approved drug for the treatment of psoriasis and multiple sclerosis. DMF is known to stabilize the transcription factor Nrf2, which in turn induces the expression of antioxidant response element genes. It has also been shown that DMF influences autophagy and participates in the transcriptional control of inflammatory factors by inhibiting NF-κB and its downstream targets. DMF is receiving increasing attention for its potential to be repurposed for several diseases. This versat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 214 publications
0
4
0
Order By: Relevance
“…Changes in the levels of the major cellular antioxidant glutathione (GSH) may lead to different forms of cell death, including apoptosis, ferroptosis and autophagy [ 45 , 46 ]. Given that DMF was previously reported to succinate GSH in other cellular models, we tested the ability of DMF to modulate the content of GSH in CLL cells.…”
Section: Resultsmentioning
confidence: 99%
“…Changes in the levels of the major cellular antioxidant glutathione (GSH) may lead to different forms of cell death, including apoptosis, ferroptosis and autophagy [ 45 , 46 ]. Given that DMF was previously reported to succinate GSH in other cellular models, we tested the ability of DMF to modulate the content of GSH in CLL cells.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, high inter-individual variability was also seen between both patients in the previous case series of Ciplea et al, with an AUC of 90 and 33 ng*h/mL, respectively. It is reported that the intake of DMF in combination with food, especially fatty food intake, can delay the peak concentration, but it is reported not to have a relevant effect on DMF subsequent exposure ( 2 , 3 ). Intake with food is also recommended to reduce flushing, which means that this combination reflects common practices, as in this case.…”
Section: Discussionmentioning
confidence: 99%
“…DMF also activates AKT pathways and thus promotes neuroprotection [ 178 ]. DMF upregulates several antioxidants including glutathione, bolstering the downstream antioxidant capacity in CNS conditions like MS, cerebral edema, TBI, and intracerebral hemorrhage [ 179 , 180 , 181 , 182 , 183 ]. DMF treatment in clinical settings has shown long-term efficacy in reducing relapse rates and minimizing lesion formation in relapsing forms of MS [ 184 ].…”
Section: Signaling Pathway Modulators For Cellular Antioxidant Synthesismentioning
confidence: 99%